La famille dans le Proche-Orient ancien (Winona Lake, Indiana)
xviii, 788 s.
Keywords: "In July, 2009, the International Association for Assyriology met in Paris, France, for 5 days to deliver and listen to papers on the theme "La famille dans le Proche-Orient." This volume, the proceedings of the conference, contains 53 of the papers read at the 55th annual Rencontre, including primarily papers directly connected with the theme and some on areas of related interest. The papers covered every period of Mesopotamian history, from the third millennium through the end of the first millennium B.C.E. The photo on the back cover shows only a representative portion of the attendees, who were warmly hosted by faculty and students from the Collège de France." --